Validation of a Double-Sandwich Enzyme-Linked Immunoassay for Pharmacokinetic Study of an rh-aFGF Hydrogel in Rat Skin and Serum - Hui, Qi; Yang, Rongshuai; Lu, Chao; Bi, Jianing; Li, Lijia; Gong, Jianxiang; Zhang, Li; Jin, Zi; Li, Xiaokun; Wang, Xiaojie (Frontiers in Pharmacology, 2020)
In this study, we validated a double sandwich enzyme-linked immunosorbent assay (ELISA) method to investigate the pharmacokinetics of rh-aFGF hydrogel in rat skin and serum. A total of 130 Sprague-Dawley rats were divided into the control group, rh-aFGF hydrogel group, and positive control group (commercial rh-aFGF-Ai). We first determined the dilution ratio of skin homogenate and then validated the quantitative range, specificity, precision, and accuracy of the ELISA method, and the stability of rh-aFGF. In the pharmacokinetic study, skin and serum samples were collected at 0.5, 1, 2, 4, 6, and 10 h after administration, and the concentration of rh-aFGF was measured by ELISA. The results show that when the skin tissue homogenate was diluted 10 times, this could avoid interference with endogenous proteins. The quantitative scope of the rh-aFGF calibration curve ranged from 62.5 to 4000 pg/mL. The precision and accuracy of rh-aFGF quality control samples were below 20%. bFGF, FGF21, KGF-2, and insulin did not interfere with the detection of aFGF, showing the method is specific. Rh-aFGF is stable under normal storage conditions. The maximum concentration (Cmax) and time to peak (Tmax) of rh-aFGF hydrogel were 909.2 pg/cm2 and 0.5 h, respectively. The relative bioavailability (F) of rh-aFGF hydrogel was 120% compared with rh-aFGF-Ai. The serum concentration of rh-aFGF was too low to be detected. The pharmacokinetics of rh-aFGF hydrogel provide further support for clinical research of rh-aFGF. This method is also a useful reference for pharmacokinetic studies of other protein drugs.